Scenario-oriented nanopesticides: Shaping nanopesticides for future agriculture - Wenjie Shangguan; Huiping Chen; Pengyue Zhao; Chong Cao; Manli Yu; Qiliang Huang; Lidong Cao (Advanced Agrochem)
Nanopesticides, as a promising technology, bring scientific and technological impetus to sustainable development and green revolution of agriculture. The excellent physicochemical properties, beneficial biological effects, and functional potential of nanopesticides have significantly contributed to improving utilization rates of pesticides, enhancing pest and disease management, and alleviating stresses. However, agricultural production and plant cultivation are diverse, leading to a wide range of application scenarios for pesticides. These application scenarios put forward more precise requirements and numerous innovative opportunities for the development of nanopesticides. Scenario-oriented nanopesticides are customized for various application scenarios and methods, aligning with the principles of economical, efficient, and sustainable future agriculture. This article outlines the development status of nanopesticides and then reviews the research progress of scenario-oriented nanopesticides, encompassing nine major application scenarios. Finally, the development priorities and prospects of scenario-oriented nanopesticides are summarized, offering innovative concepts for advancement of nanopesticides.